نظم دعم القرار واختيار الأداة الملائمة لبنائها (Journal of Accounting and Financial Studies ( JAFS ), 2011)
DSS are the result of the information technology.  DSS focus on providing the relative support to improve the quality of decision making in the organization.  The quality of decisions depends on the information availability and the adequate models of analysis.  DSS have evolved since the 1970's.  The globalization and the organizational complexity have strongly effect the DSS development.  The purpose of this research work is to shed the light on the essence of DSS, its tools (OLAP, Web-Based……..), and to provide a framework to assist the Iraq organization in selecting the appropriate DSS tool for implementation.  This research is important because it highlights the role of DSS and their evolutions which reflect many technological and managerial implications on the Iraqi organization as to how far or close it is to the developments in this field.  The research concluded that the Iraqi organization is still away from the up-to-date progress in DSS, and that it should start applying DSS that are based on the World Wide Web to reduce time, effort, and cost in making sound decisions.